The Nanking Atrocity: Still and Moving Images 1937–1944 - Gary Evans (Media and Communication, 2014)
This manuscript investigates the facts of publication of the images of the Nanking Atrocity (December 1937–January 1938) in LIFE and LOOK magazines, two widely read United States publications, as well as the Nanking atrocity film clips that circulated to millions more in American and Canadian newsreels some years later. The publishers of these images were continuing the art of manipulation of public opinion through multimodal visual media, aiming them especially at the less educated mass public. The text attempts to describe these brutal images in their historical context. Viewing and understanding the underlying racial context and emotive impact of these images may be useful adjuncts to future students of World War II. If it is difficult to assert how much these severe images changed public opinion, one can appreciate how the emerging visual culture was transforming the way that modern societies communicate with and direct their citizens' thoughts.